Analysis of Heart Pulse Transmission Parameters Determined from Multi-Channel PPG Signals Acquired by a Wearable Optical Sensor - Přibil Jiří; Přibilová Anna; Frollo Ivan (Measurement Science Review, 2023)
The article describes the development and testing of a special prototype wearable device consisting of three optical photoplethysmography (PPG) sensors. The functionality of the developed triple PPG sensor was tested under normal laboratory conditions and in a running magnetic resonance imaging (MRI) scanner working with a low magnetic field. The results of the first measurements under normal laboratory conditions show that the obtained mutual positions of systolic/diastolic blood pressure values and heart pulse transmission parameters determined from the PPG waves can be fitted by a line segment with a sufficiently high slope. Measurement experiments inside the open-air MRI tomograph show the practical influence of vibrations and acoustic noise on the cardiac system of the examined persons, which was confirmed by a slight increase in the heart pulse rate and changes in pulse transmission time and pulse wave velocity. We plan to perform further measurements inside the whole-body MRI device producing more intensive vibrations and noise with expected higher stress impact on an exposed person.